Treatment of Neck and Back Pain - Deiva Sigamani Vinayagam; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2007)
An attempt to provide knowledge in treatment techniques to implement therapy and care of a person who is suffering from upper back and lower back pain with various pathological medical conditions. This book includes information about how to implement therapeutic way of healing the back pain by correct selection of physical therapy approaches and do$1 (Bs and don$1 (Bts for the day-today daily activities. Presents a multidimensional approach towards cervical, thoracic and lumbosacral pains, their diagnosis and management. This book will help the health care providers and back pain sufferers.s
Keywords: Physiotherapy; Electronic books